Site-Directed Spin Labeling EPR Spectroscopy for Determination of Albumin Structural Damage and Hypoalbuminemia in Critical COVID-19 - Ekaterina Georgieva; Yanka Karamalakova; Georgi Arabadzhiev; Vasil Atanasov; Rositsa Kostandieva; Mitko Mitev; Vanya Tsoneva; Yovcho Yovchev; Galina Nikolova (MDPI AG, 2022)
The main factors in the COVID-19 pathology, which can initiate extensive structural changes at the cellular and molecular levels, are the generation of free radicals in abnormal amounts, and oxidative stress. Under "oxidative shock" conditions, the proteins undergo various modifications that affect their function and activity, and as a result distribute malfunctioning protein derivatives in the body. Human serum albumin is a small globular protein characterized by a high overall binding capacity for neutral lipophilic and acidic dosage forms. The albumin concentration is crucial for the maintenance of plasma oncotic pressure, the transport of nutrients, amino acids, and drugs, the effectiveness of drug therapy, and the prevention of drug toxicity. Hypoalbuminemia and structural defects molecule in the protein suggest a risk of changed metabolism and increased plasma concentration of unbound drugs. Therefore, the albumin structural and functional changes accompanied by low protein levels can be a serious prerequisite for ineffective therapy, frequent complications, and high mortality in patients with SARS-CoV-2 infection. The current opinion aims the research community the application of Site-Directed Spin Labeling Electron Paramagnetic Resonance spectroscopy (SDSL-EPR) and 3-Maleimido-PROXYL radical in determining abnormalities of the albumin dynamics and protein concentrations in COVID-19 critical patients.